Further investigation of the six-DOF hollow gravity anchor: Impact of the internal slant angle. (November 2017) - Cai, Wen-Hao; Zhan, Jie-Min; Gong, Ye-Jun; Hu, Wen-Qing
Abstract: Our recent study on the new type hollow gravity anchor shows that the hollow anchor can save the anchoring time and decrease the anchoring deviation, compared with the traditional solid anchor. This study aims to do further research on the internal structure of the hollow anchor using the developed motion-based zonal mesh update (MBZMU) method. However, though the validated MBZMU method is able to capture the large-scale six-DOF motion of the gravity anchor, the tested cases in the previous study did not reflect the sway-yaw-roll motion of the gravity anchor. Instead of the imperfect one camera calibration method, two orthorhombic high-speed cameras are adopted in this study to record the six-DOF anchoring process. Additionally, quaternions are introduced to quantitate the anchor rotation to avoid the singularity problem caused by Euler angles. The experimentally measured trajectory path of the six-DOF gravity anchor is consistent with the numerical simulated result. Furthermore, one optimal internal slant angle is observed, through a comparative on the six-DOF anchoring processes of the hollow anchors with different internal slant angles, which are the key factor determining the inlet flow rate through the central water channel of the hollow anchor. Highlights: Two camera calibration method, self-designed release device and quaternions are introduced to further the study on six-DOF anchoring process. Not only heave-surge-pitch motions, but also sway-yaw-roll motions of the gravity anchor are validated. The hollow gravity anchor with optimized internal slant angle has smaller anchoring time and deviation than those of the traditional solid anchor.